PSYCHOLOGICAL SIGNIFICANCE OF STUDYING THE PRIORITY QUALITIES OF TABLE TENNIS PLAYERS (British Journal of Global Ecology and Sustainable Development, 2023)
This article reveals the psychological significance of the individual qualities of highly qualified table tennis players, which are important for ensuring victory in the competition process.